2016
DOI: 10.1542/peds.2016-0331
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Chronic Pain: Biopsychosocial Assessment and Formulation

Abstract: Chronic pain in children is an increasingly recognized clinical problem with alarmingly high prevalence rates found in some populations. Although it is not understood why some children experience high levels of pain, the subjective experience of chronic pain (including its site, intensity, quality, unpleasantness, and associated suffering) has long been believed to result from interactions between multiple contributors, including nociceptive, affective, sociocultural, behavioral, and cognitive. Regardless of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(145 citation statements)
references
References 152 publications
1
119
0
18
Order By: Relevance
“…This is problematic given the current recommendation for multimodal care to thoroughly address biopsychosocial contributors to pediatric chronic pain. 11 Although pediatric pain research is growing rapidly, 12 there remains a disconnect between existing scientific evidence and current clinical practice, a further challenge to developing pediatric chronic pain policy. 13 Estimates suggest that it can take up to 17 years for research to impact patient care, 14 and many children and adolescents with chronic pain struggle to access evidence-based treatment.…”
mentioning
confidence: 99%
“…This is problematic given the current recommendation for multimodal care to thoroughly address biopsychosocial contributors to pediatric chronic pain. 11 Although pediatric pain research is growing rapidly, 12 there remains a disconnect between existing scientific evidence and current clinical practice, a further challenge to developing pediatric chronic pain policy. 13 Estimates suggest that it can take up to 17 years for research to impact patient care, 14 and many children and adolescents with chronic pain struggle to access evidence-based treatment.…”
mentioning
confidence: 99%
“…Pediatric chronic pain is complex, with nociceptive, affective, sociocultural, behavioral, and cognitive components, and therefore requires multimodal management [24]. A systematic review on the epidemiology of chronic pain in children and adolescents found the prevalence rates of pain to be 8-83% for headaches, 4-53% for abdominal pain, 14-24% for back pain, 4-40% for musculoskeletal pain, 4-49% for multiple pains, and 5-88% for other pains.…”
Section: Reviewmentioning
confidence: 99%
“…A biopsychosocial approach to assessment and management of pain has been recommended for both adults [68] and children. [116]. Many psychosocial factors influence the development and trajectory of chronic pain, and may encompass "general" variables (eg.…”
Section: Psychosocial Factorsmentioning
confidence: 99%